Energy-saving clustering routing algorithm based on semi-fixed cluster for wireless sensor networks - ZHANG Zhaohui; ZHOU Jiaqi (Tongxin xuebao)
To solve the problems of short network lifetime, caused by unbalanced node energy consumption, and large energy consumption in data transmission of wireless sensor network, a semi-fixed clustering routing algorithm was proposed in order to achieve the load balance of each cluster. After the nodes were deployed, each cluster was adjusted to ensure that each cluster was well-matched in the number of nodes. In the beginning, the cluster heads were selected according to the distances between nodes and the residual energy of nodes. In data transmission phase, the optimization model of relay nodes was constructed according to the residual energy of nodes, the distances between nodes and the base station, and the distances between nodes. Then the goal of balancing and reducing energy consumption was achieved. Furthermore, when the network ran for a period of time, due to the large differences in residual energy between clusters, the clusters were optimized again to make the energy of each cluster as close as possible. Finally, when the energy of cluster heads was lower than the set threshold, the cluster heads were rotated and optimized again to extend the working life of nodes. The simulation results show that the proposed algorithm reduces the energy consumption of nodes and provides longer network lifetimes of WSN.